Answer:
a. [tex]c(x) = 2x + 105[/tex]
b. [tex]c(50) =\$205[/tex]
Step-by-step explanation:
The variable cost of $ 2 implies that for each manufactured calculator the total cost increases $ 2.
The fixed cost of $ 105 implies that regardless of the number of manufactured calculators there will always be a cost of $ 105.
If we call x the number of manufactured calculators then the total cost c(x) will be:
[tex]c(x) = 2x + 105[/tex]
Then, the cost of manufactured 50 calculators a day is:
[tex]c(50) = 2(50) + 105[/tex]
[tex]c(50) = 100 + 105[/tex]
[tex]c(50) =\$205[/tex]
To divide two fractions, first rewrite the problem as the dividend times the ______ of the divisor.
Answer:
reciprocal
Step-by-step explanation:
Final answer:
To divide two fractions, rewrite the operation as the first fraction multiplied by the reciprocal of the second. Multiplication of fractions involves simply multiplying the numerators and denominators, then simplifying by any common factors.
Explanation:
To divide two fractions, first rewrite the problem as the dividend times the reciprocal of the divisor. When dividing by a fraction, it is equivalent to multiplying by the reciprocal of that fraction. For example, dividing by ⅓ is the same as multiplying by 3 (the reciprocal of ⅓). Similarly, multiplying by ½ is the same as dividing by 2 because ½ is the reciprocal of 2. To multiply fractions, simply multiply the numerators together and the denominators together, simplifying by any common factors as necessary.
Demonstrating this concept through an example, let’s consider the division of 4 by ⅓. First, we find the reciprocal of ⅓, which is 3, and then we multiply 4 by 3 to get 12. Through the multiplication of fractions, if we have ⅛ multiplied by ⅓, we would multiply the numerators (2 and 1) and the denominators (8 and 3), and then simplify the resulting fraction by canceling out any common factors.
What is the relationship between the pair of angles ABC and LMN shown
in the diagram below?
A. they are supplementary angles
B.they are complementary angles
C.they are adjacent angles
D.they are vertical angles
Answer:
the answer is B
Step-by-step explanation:
the sum of both angles is 90 degree.
By definition if the sum of two angles is 180 is supplementary
If the sum of two angles is 90 is complementary
Then, 70 + 20 =90 degree
So, They are complementary angles
Answer:
Option B.
Step-by-step explanation:
Measure of ∠ABC = 20°
and measure of ∠NML = 70°
Then ∠ABC + ∠NML = 20 + 70
= 90°
Therefore, ∠ABC and ∠NML are complementary angles because sum of complementary angles is 90°.
find the slope of a line that passes through (3, 6) and. (5, 3) a. -3/2 b. 3/2 c. 2/3
Answer:
option a
Step-by-step explanation:
To find the slope 'm' we use 2 points from the line, those are given in the statement:
[tex]x_{1} =3\\y_{1} =6\\\\x_{2} =5\\y_{2} =3\\m=\frac{y_{2} -y_{1} }{x_{2}-x_{1}}\\m=\frac{3 -6 }{5-3}}\\m=\frac{-3 }{2}}[/tex]
An interval has the notation (2,14). Find the
distance from the midpoint of the interval to
either endpoint.
Answer:
The distance from the midpoint of the interval to either endpoint is 6 units
Step-by-step explanation:
step 1
Find the midpoint of the interval
The formula to calculate the midpoint between two numbers is equal to
[tex]M=(\frac{x1+x2}{2})[/tex]
substitute
[tex]M=(\frac{2+14}{2})[/tex]
[tex]M=8[/tex]
step 2
Find the distance from the midpoint of the interval to either endpoint.
14-8=6 units
or
8-2=6 units
therefore
The distance from the midpoint of the interval to either endpoint is 6 units
To find the distance from the midpoint of the interval (2,14) to either endpoint, first find the midpoint, which is 8, then calculate the distance to either endpoint by subtracting the lower endpoint from the midpoint, resulting in a distance of 6 units.
The question asks to find the distance from the midpoint of the interval (2,14) to either endpoint. To start, we find the midpoint of the interval by adding the two endpoints together and dividing by 2:
Midpoint = \((2 + 14) / 2\) = \(16 / 2\) = 8
Next, we calculate the distance from the midpoint to one of the endpoints. The distance can be found by subtracting the lower endpoint from the midpoint:
Distance = \(8 - 2\) = 6
Therefore, the distance from the midpoint of the interval to either endpoint is 6 units.
Suppose a bus arrives at a bus stop every 40 minutes. If you arrive at the bus stop at a random time, what is the probability that you will have to wait at least 10 minutes for the bus? Write the probability as a simplified fraction.
plzzzz help hahaha
Answer:
=3/4
Step-by-step explanation:
A bus arrives at a bus stop every 40 minutes.
You arrive at a bus stop at a random time.
So, probability that you will wait at most 10 minutes = 10/40
So, The probability that you will wait at least 10 minutes= 1-10/40
=1- 10/40
By taking L.C.M we get;
=40-10/40
=30/40
=3/4
Thus the probability that you will have to wait at least 20 minutes for the bus is 3/4....
Answer:
3/4
Step-by-step explanation:
hahahaha to you asell
QUICK! 75 POINTS !!Select all that are part of the solution set of csc(x) > 1 and over 0 ≤ x ≤ 2π.
Answer:
[tex]\frac{\pi}{4}[/tex]
[tex]\frac{5\pi}{6}[/tex]
Step-by-step explanation:
The answer uses the unit circle and that sine and cosecant are reciprocals.
The first choice doesn't even fit the criteria that [tex]x[/tex] is between [tex]0[/tex] and [tex]2\pi[/tex] (inclusive of both endpoints) because of the [tex]x=\frac{-7\pi}{6}[/tex].
Let's check the second choice.
[tex]\csc(\frac{\pi}{4})=\frac{2}{\sqrt{2}} \text{ since } \sin(\frac{\pi}{4})=\frac{\sqrt{2}}{2}[/tex].
[tex]\csc(\frac{\pi}{4})>1 \text{ since } \frac{2}{\sqrt{2}}>1[/tex]
[tex]\csc(\frac{\pi}{2})=1 \text{ since } \sin(\frac{\pi}{2})=1[/tex] which means [tex]\csc(\frac{\pi}{2})=1[/tex] which is not greater than 1.
So we can eliminate second choice.
Let's look at the third.
[tex]\csc(\frac{5\pi}{6})=2 \text{ since } \sin(\frac{5\pi}{6})=\frac{1}{2}[/tex] which means [tex]\csc(\frac{5\pi}{6})>1[/tex].
[tex]\csc(\pi)[/tex] isn't defined because [tex]\sin(\pi)=0[/tex].
So we are eliminating 3rd choice now.
Let's look at the fourth choice.
[tex]\csc(\frac{7\pi}{6})=-2 \text{ since } \sin(\frac{7\pi}{6})=\frac{-1}{2}[/tex] which means [tex]\csc(\frac{7\pi}{6})<1[/tex] and not greater than 1.
I was looking at the rows as if they were choices.
Let me break up my choices.
So we said [tex]x=-\frac{7\pi}{6}[/tex] doesn't work because it is not included in the inequality [tex]0\le x \le 2\pi[/tex].
How about [tex]x=0[/tex]? This leads to [tex]\csc(0)[/tex] which doesn't exist because [tex]\sin(0)=0[/tex].
So neither of the first two choices on the first row.
Let's look at the second row again.
We said [tex]\frac{\pi}{4}[/tex] worked but not [tex]\frac{\pi}{2}[/tex]
Let's look at the choices on the third row.
We said [tex]\frac{5\pi}{6}[/tex] worked but not [tex]x=\pi[/tex]
Let's look at at the last choice.
We said it gave something less than 1 so this choice doesn't work.
Answer:x=pi/4 and x=5pi/6
Step-by-step explanation:
on edge just did it
What is the solution to the system of equations?
Answer:
(-10, 2, 6)Step-by-step explanation:
[tex]\left\{\begin{array}{ccc}x+3y+2z=8&(1)\\3x+y+3z=-10&(2)\\-2x-2y-z=10&(3)\end{array}\right\qquad\text{subtract both sides of the equations (1) from (2)}\\\\\underline{-\left\{\begin{array}{ccc}3x+y+3z=-10\\x+3y+2z=8\end{array}\right }\\.\qquad2x-2y+z=-18\qquad(4)\qquad\text{add both sides of the equations (3) and (4)}\\\\\underline{+\left\{\begin{array}{ccc}-2x-2y-z=10\\2x-2y+z=-18\end{array}\right}\\.\qquad-4y=-8\qquad\text{divide both sides by (-4)}\\.\qquad\qquad y=2\qquad\text{put the value of y to (1) and (3)}[/tex]
[tex]\left\{\begin{array}{ccc}x+3(2)+2z=8\\-2x-2(2)-z=10\end{array}\right\\\left\{\begin{array}{ccc}x+6+2z=8&\text{subtract 6 from both sides}\\-2x-4-z=10&\text{add 4 to both sides}\end{array}\right\\\left\{\begin{array}{ccc}x+2z=2&\text{multiply both sides by 2}\\-2x-z=14\end{array}\right\\\underline{+\left\{\begin{array}{ccc}2x+4z=4\\-2x-z=14\end{array}\right}\qquad\text{add both sides of the equations}\\.\qquad\qquad3z=18\qquad\text{divide both sides by 3}\\.\qquad\qquad z=6\qquad\text{put the value of z to the first equation}[/tex]
[tex]x+2(6)=2\\x+12=2\qquad\text{subtract 10 from both sides}\\x=-10[/tex]
the sets e and f are given below
E= (-2, -1,3,5,6,7)
F=(-2,2,6)
what is the intersection of e and f
find the union of e and f
write your answers using set notation
Intersection of two sets E and F is set G which contains elements x that are common to set E and set F.
[tex]G=E\cap F=\{x; x\in E\wedge x\in F\}[/tex]
Here G is,
[tex]G=\{-2,6\}[/tex]
Union of two sets E and F is a set H which contains all elements x that occur in set E or set F.
[tex]H=E\cup F=\{x; x\in E\vee x\in F\}[/tex]
Hence,
[tex]H=\{-2,-1,2,3,5,6,7\}[/tex]
Hope this helps.
r3t40
The intersection of sets E and F: E ∩ F = {-2, 6}
The union of sets E and F: E U F = {-2, -1, 2, 3, 5, 6, 7}
Solve kx - 2 = 7 for x
ОА. x-
Ов. х = 9
Ос. х = 9 - k
Op. x-
Answer:
The solution of kx-2=7 is x = 9/k
Step-by-step explanation:
Given:
kx-2 = 7
In order to get the solution of the given equation, we have to isolate x so that we can determine its value.
Adding 2 on both sides
kx-2+2 = 7+2
kx = 9
Dividing both sides by k
kx/k = 9/k
x = 9/k
Therefore, the solution of kx-2=7 is x = 9/k ..
Answer:
X=9/k
Step-by-step explanation:
^^^ person is right
Find x. Assume that any segment that appears to be tangent is tangent.
Select one:
A. 10
B. 5
C. 12
D. 15
Answer:
Option D. x=15°
Step-by-step explanation:
we know that
The measurement of the outer angle is the semi-difference of the arcs it encompasses.
see the attached figure to better understand the problem
∠x=(1/2)[arc AB-arc CD]
arc AB=40°
Remember that the diameter divide the circle into two equal parts
arc CD=180°-(130+40)°=10°
substitute
∠x=(1/2)[40°-10°]=15°
Answer:
x = 15!
Step-by-step explanation:
I got it right on my in class exercise!
what is the domain of the function shown in the mapping?
a. x|x=-5, -3, 1, 2, 6
b. y|y=-9, -6, 0, 2, 4
c. x|x= -9, -6, -5, -3, 0, 1, 2, 4, 6
d. y|y= -9, -6, -5, -3, 0, 1, 2, 4, 6
Answer:
it's A
Step-by-step explanation:
The domain is all the input values which is x|x=-5,-3,1,2,6
Use the quadratic formula to solve the equation -3x2-x-3=0
Answer:
[tex]x=\frac{1+\sqrt{35}i}{-6}\,\, and\,\, x=\frac{1-\sqrt{35}i}{-6}\\[/tex]
Step-by-step explanation:
the quadratic formula is:
[tex]x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]
a= -2, b = -1 and c =-3
Putting values in the formula
[tex]x=\frac{-(-1)\pm\sqrt{(-1)^2-4(-3)(-3)}}{2(-3)}\\x=\frac{1\pm\sqrt{-35}}{-6}\\x=\frac{1+\sqrt{-35}}{-6}\,\, and\,\, x=\frac{1-\sqrt{-35}}{-6}\\We\,\, know \,\,that \,\,\sqrt{-1} = i \\x=\frac{1+\sqrt{35}i}{-6}\,\, and\,\, x=\frac{1-\sqrt{35}i}{-6}\\[/tex]
So, [tex]x=\frac{1+\sqrt{35}i}{-6}\,\, and\,\, x=\frac{1-\sqrt{35}i}{-6}\\[/tex]
Answer:
Using quadratic formula, the solution to this equation is the roots of the equations given are ; x = 1+√35i / -6 or x = 1-√35i / -6
Step-by-step explanation:
-3x² - x - 3=0
To solve this using quadratic formula, we will first of all write down the quadratic formula
x = -b ±√b²- 4ac / 2a
From the above question;
a = -3 b = -1 and c=-3
So we can now proceed to plug-in our variable
x = -(-1) ± √(-1)² - 4(-3)(-3) / 2(-3)
x= 1±√1-36 / -6
x = 1 ±√-35 / -6
x=1 ± √35 · √-1 /-6
x = 1±√35 i / -6
Note the square root of negative 1 is i
Either x = 1+√35i / -6 or x = 1-√35i / -6
Therefore the roots of the equations given are ; x = 1+√35i / -6 or x = 1-√35i / -6
What is the slope and y-intercept of the equation 6x - 1 = 3y - 10?
A. m=2, b = 3
B. m= 2, b = -3
C. m= 3, b= 4
D. m= 6, b= 9
Answer: A. M=2, y int=3
Step-by-step explanation:
In slope intercept form the equation is y=2x+3, in the formula y=mx+b m=slope and b=y intercept.
The slope and y-intercept of the equation 6x - 1 = 3y - 10 is Option(A) m=2, b = 3 .
What is slope and y-intercept ?The slope of a straight line is the measure of its inclination or tangent to the point of the straight line.
The y-intercept gives the value of the y-coordinate where the straight line intercepts with the y-axis.
For general representation of a straight line y = mx + c , the slope is the value of m and its y-intercept is c.
How to find the slope and y-intercept of given equation ?The given equation is 6x - 1 = 3y - 10 .
⇒ 3y = 6x + 10 - 1
⇒ 3y = 6x + 9
∴ y = 2x + 3
Comparing with the general equation of straight line, y = mx + c we get slope = 2 and y-intercept = 3.
Thus, the slope and y-intercept of the equation 6x - 1 = 3y - 10 is Option(A) m=2, b = 3 .
To learn more about slope refer -
https://brainly.com/question/3493733
#SPJ2
If f(x) = 4* + 12x and g(x) = 5x - 1, find (f + g)(x).
Answer:
[tex]\large\boxed{(f+g)(x)=4^x+17x-1}[/tex]
Step-by-step explanation:
[tex](f+g)(x)=f(x)+g(x)\\\\f(x)=4^x+12x,\ g(x)=5x-1\\\\(f+g)(x)=(4^x+12x)+(5x-1)=4^x+17x-1[/tex]
According to the rules of NCAA volleyball, there must be exactly 6 players on the court at all times and each player has a unique designated position on the court. How many different starting position configurations are possible for the 6 starting players of a volleyball team that follows this rule?
Answer:
720
Step-by-step explanation:
permutation formula=
n!/(n-r)!
There are 720 different starting position configurations possible for the 6 starting players of a volleyball team that follows the rule.
We have
To determine the number of different starting position configurations for a volleyball team with 6 players, we can use the concept of permutations.
Since each player has a unique designated position on the court, we can think of this as arranging 6 distinct objects (the players) in 6 distinct positions (the court positions).
The number of possible arrangements can be calculated using the formula for permutations, denoted as "n P r," which represents the number of ways to select and arrange r objects from a set of n objects.
In this case, we want to arrange 6 players in 6 positions, so we can calculate 6 P 6:
6 P 6 = 6!
Using the formula for factorial:
6! = 6 * 5 * 4 * 3 * 2 * 1
= 720
Therefore,
There are 720 different starting position configurations possible for the 6 starting players of a volleyball team that follows the rule of having exactly 6 players on the court, each with a unique designated position.
Learn more about permutations here:
https://brainly.com/question/32683496
#SPJ2
What is the solution to the following system of equations?
X – 3y = 6
2x + 2y = 4
A.y=-1
B.x=3
C.y=3
D.x=-1
Answer:
x = 3, y = -1 ⇒ ABStep-by-step explanation:
[tex]\left\{\begin{array}{ccc}x-3y=6&\text{multiply both sides by (-2)}\\2x+2y=4\end{array}\right\\\\\underline{+\left\{\begin{array}{ccc}-2x+6y=-12\\2x+2y=4\end{array}\right}\qquad\text{add both sides of the equations}\\.\qquad\qquad8y=-8\qquad\text{divide both sides by 8}\\.\qquad\qquad y=-1\\\\\text{Put the value of y to the first equation:}\\\\x-3(-1)=6\\x+3=6\qquad\text{subtract 3 from both sides}\\x=3[/tex]
Answer: y = -1 and x = 3
Step-by-step explanation:
x - 3y = 6 --------(1)
2x + 2y = 4 -------(2)
we multiply (1) by 2
2x - 6y = 12 --------(3)
(3) - (1)
-8y = 8
y = -1
Putting y = -1 into equation (1)
x - 3 (-1) = 6
x + 3 =6
collect the like term
x = 6 - 3
x = 3
Therefore x= 3 and y = -1
25 POINTS PLEASE HELP
Let f(x) = (6x^3 - 7)^3 and g(x) = 6x^3- 7.
Given that f(x) = (hºg)(x), find h(x).
Enter the correct answer
Answer:
[tex]\large\boxed{h(x)=x^3}[/tex]
Step-by-step explanation:
[tex]f(x)=(6x^3-7)^3\\\\(h\circ g)(x)=h\bigg(g(x)\bigg)\to\text{exchange x to}\ g(x)=6x^3-7\\\\f(x)=(\underbrace{6x^3-7}_{g(x)})^3=\bigg(g(x)\bigg)^3=h\bigg(g(x)\bigg)\\\\\text{Therefore}\ h(x)=x^3[/tex]
find the value of this expression if x=-7 and y=-2. xy/9
Answer:
The value is 14/9.
Step-by-step explanation:
xy/9
Put the value of x= -7 and y= -2 in the expression.
=(-7) (-2)/9
=14/9
Translate each phrase into an algebraic expression.
the quotient of thirty and three times a number
Answer:
30/3x
Step-by-step explanation:
Let
x ----> a number
we know that
The algebraic expression of the phrase" thirty" is equal to the number 30
The algebraic expression of the phrase"three times a number" is equal to multiply the number by 3 ----> 3x
therefore
"The quotient of thirty and three times a number" is equal to divide the number 30 by 3x
30/3x
Answer: The correct option is (B) [tex]\dfrac{30}{3x}.[/tex]
Step-by-step explanation: We are given to translate the following phrase into an algebraic expression :
"the quotient of thirty and three times a number."
Let the unknown number be represented by x.
Then, according to the given phrase, the algebraic expression can be written as :
[tex]E=\dfrac{30}{3\times x}\\\\\\\Rightarrow E=\dfrac{30}{3x}.[/tex]
Thus, the required algebraic expression is [tex]\dfrac{30}{3x}.[/tex]
Option (B) is CORRECT.
A line crosses the coordinates (-3, 5) and (4, -2). What is the slope-intercept form of the equation of this line?
[tex]\bf (\stackrel{x_1}{-3}~,~\stackrel{y_1}{5})\qquad (\stackrel{x_2}{4}~,~\stackrel{y_2}{-2}) \\\\\\ slope = m\implies \cfrac{\stackrel{rise}{ y_2- y_1}}{\stackrel{run}{ x_2- x_1}}\implies \cfrac{-2-5}{4-(-3)}\implies \cfrac{-7}{4+3}\implies \cfrac{-7}{7}\implies -1 \\\\\\ \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-5=1[x-(-3)]\implies y-5=1(x+3) \\\\\\ y-5=x + 3\implies y=x+8[/tex]
What is the average rate of change for this function for the interval from x=3 to x=5?
Answer:
B
Step-by-step explanation:
The average rate of change of f(x) in the closed interval [ a, b ] is
[tex]\frac{f(b)-f(a)}{b-a}[/tex]
Here [ a, b ] = [ 3, 5 ]
From the table of values
f(b) = f(5) = 32
f(a) = f(3) = 8
Hence
average rate of change = [tex]\frac{32-8}{5-3}[/tex] = [tex]\frac{24}{2}[/tex] = 12
Answer:
The average rate of change is [tex]12[/tex]
Step-by-step explanation:
Given:
Interval; x = 3 to x = 5
We'll represent these by
x1 = 3
x2 = 5
The corresponding y values are:
When x = 3, y = 8
When x = 5, y = 32
This will also be represented
y1 = 8
y2 = 32
Average rate of change is then calculated as follows
[tex]m = \frac{y_{2} - y_{1}}{x_{2} - x_{1}}[/tex]
Where m represent average rate of change
By Substitution, we have
[tex]m = \frac{32 - 8}{5 - 3}[/tex]
[tex]m = \frac{24}{2}[/tex]
[tex]m = 12[/tex]
Hence, the average rate of change is [tex]12[/tex]
What is cavalieris principle
Step-by-step explanation:
Cavalieri's Principle. A method, with formula given below, of finding the volume of any solid for which cross-sections by parallel planes have equal areas. This includes, but is not limited to, cylinders and prisms.
Last week Bill made a purchase of $56.78 before tax. This week, the same items on sale would have cost him $41.90 before tax. If the tax is 4%, how much could Bill have saved by buying the items on sale (including tax)?
Prove that the diagonals of a rectangle bisect each other.
The midpoint of AC is _____
Answer:
(a,b)
Step-by-step explanation:
simply we find the midpoint of AC and the midpoint of Bd by dividing over 2
Answer:
We choose D.
Step-by-step explanation:
Let the midpoint is O
We will use Angle-SIde-Angle principle to prove that the diagonals of a rectangle bisect each other.
Have a look at the two triangles: AOB and DOC, they are congruent because:
AB = DC ∠OAB = ∠DCO because they are alternate angles∠OBA = ∠CDO because they are alternate anglesSo we can conclude that: OB = OB when two triangles: AOB and DOC are congruent.
Similar, apply for the two triangles: AOD and BOC are congruent so we have OA = OC .
=> It proves that the point O simultaneously is the midpoint and intersection point for the diagonals.
=> The midpoint of AC is ([tex]\frac{2a+ 0}{2}[/tex] , [tex]\frac{0 + 2b}{2}[/tex] ) = (a, b), we choose D.
Help me if you can attachment linked
Thank You
Answer:
B) 4
Step-by-step explanation:
Tan is opposite/adjacent. That means that 3 is the opposite side while 4 is the adjacent side.
evaluate 625-625÷25-25
Hi !
625 - (625 ÷ 25) - 25 = 575
Answer:
575
Step-by-step explanation:
Following the order of operations, division is performed before subtraction
Given
625 - 625 ÷ 25 - 25 ← perform the division
= 625 - 25 - 25 ← now perform the subtraction
= 600 - 25
= 575
carlos cut 5/12 of a yard of cloth into 5 pieces of equal length . what was the length. of each piece of cloth ?
Answer:
The length of each piece of cloth =1/12 yard
Step-by-step explanation:
Number of pieces = 5
Carlos cut 5/12 of a yard of cloth
Length of each piece = ?
To find the length of each piece simply divide 5/12 by 5.
Length of each piece of cloth = 5/12/5
Length of each piece of cloth =5/12 * 1/5
Length of each piece of cloth=1/12
Therefore the length of each piece of cloth =1/12 yard....
Answer:
the answer is a
Step-by-step explanation:
which of the following is the graph of the inequality y>-2x+3
The answer is " D. Graph D"
Use the recursive formula f(n) = 0.4 . f(n-1) + 12 to determine the 2nd term if f(1) = 4.
A. f(2) = 12.6
B. f(2) = 13.2
C. f(2) = 13.6
D. f(2) = 14.2
Answer:
Assuming you have [tex]f(n)=0.4f(n-1)+12[/tex] with [tex]f(1)=4[/tex], the answer is f(2)=13.6.
Step-by-step explanation:
I think that says [tex]f(n)=0.4f(n-1)+12[/tex] with [tex]f(1)=4[/tex].
Now we want to find [tex]f(2)[/tex] so replace n with 2:
This gives you:
[tex]f(2)=0.4f(2-1)+12[/tex]
[tex]f(2)=0.4f(1)+12[/tex]
[tex]f(2)=0.4(4)+12[/tex]
[tex]f(2)=1.6+12[/tex]
[tex]f(2)=13.6[/tex]
Answer:
13.6 (Answer C)
Step-by-step explanation:
I think you meant f(n) = 0.4 * f(n-1) + 12, where * represents multiplication.
Then f(2) = 0.4 * (4) + 12, or 1.6 + 12, or 13.6.
What is the common difference in this sequence: 4, 13, 22, 31, 40?
Answer:
9
Step-by-step explanation:
To find the common difference, take the second term and subtract the first term
13-4 =9
Lets check:
Take the third term and subtract the second term
22-13 =9
The common difference is 9
Answer:
9
Step-by-step explanation:
9 is the common difference between the numbers in this sequence
4 +9 = 13
13 +9 = 22
22 +9 = 31
31 +9 = 40
Therefore the common difference is 9
PLEASE DO MARK ME AS BRAINLIEST IF MY ANSWER IS HELPFUL ;)